Pengaruh Media Sosial Tiktok terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Bahasa Indonesia Fase C di SDN 007 Teratak Air Hitam - Anggi Mailinda Sari (Jurnal Pendidikan Dirgantara, 2025)
TikTok social media has become an integral part of students' daily lives, yet its use in the educational context remains a topic of debate. This study aims to determine the influence of TikTok usage on students' learning outcomes in the Indonesian language subject for Phase C at SDN 007 Teratak Air Hitam. A quantitative approach with a correlational method was employed. Data collection techniques included the distribution of questionnaires and documentation of learning outcomes. Statistical test results indicated no significant influence of TikTok usage on students' learning outcomes. The conclusion of this study is that students’ use of TikTok does not have a meaningful impact on their Indonesian language learning achievement, suggesting the need for control and guidance to ensure it does not disrupt the learning process.